Patients' satisfactions on the waiting period at the emergency units. Comparison study before and during COVID-19 pandemic - Abdelhakim Abdelhadi (SAGE Publishing, 2021)
Background: This paper analyzes the patients' experience and satisfaction regarding the waiting period at the emergency unit's hospital before and during the COVID-19 pandemic. Design and methods: Brainstorming methodology and data analysis from the public domain used on male and female patients in a private hospital in a middle eastern country. The data analyzed seek the patients' level of satisfaction about the waiting period before entering the treatment area, inside the treatment area before the doctor's check, and during the rest period after the doctor's visit. The customer's satisfaction is a significant measure during the COVID-19 pandemic, as it may affect the patient's perspective of the facility. A paired t-test at 95% confidence level was conducted. Results and Conclusions: The results indicated no difference in satisfaction of the period spent in the emergency room before and during the pandemic.